In Silico Identification of Three Types of Integrative and Conjugative Elements in Elizabethkingia anophelis Strains Isolated from around the World - Xu, Jiannong (mSphere, 2019)
Elizabethkingia anophelis is an emerging global multidrug-resistant opportunistic pathogen. We assessed the diversity among 13 complete genomes and 23 draft genomes of E. anophelis strains derived from various environmental settings and human infections from different geographic regions around the world from 1950s to the present. Putative integrative and conjugative elements (ICEs) were identified in 31/36 (86.1%) strains in the study. A total of 52 putative ICEs (including eight degenerated elements lacking integrases) were identified and categorized into three types based on the architecture of the conjugation module and the phylogeny of the relaxase, coupling protein, TraG, and TraJ protein sequences. The type II and III ICEs were found to integrate adjacent to tRNA genes, while type I ICEs integrate into intergenic regions or into a gene. The ICEs carry various cargo genes, including transcription regulator genes and genes conferring antibiotic resistance. The adaptive immune CRISPR-Cas system was found in nine strains, including five strains in which CRISPR-Cas machinery and ICEs coexist at different locations on the same chromosome. One ICE-derived spacer was present in the CRISPR locus in one strain. ICE distribution in the strains showed no geographic or temporal patterns. The ICEs in E. anophelis differ in architecture and sequence from CTnDOT, a well-studied ICE prevalent in Bacteroides spp. The categorization of ICEs will facilitate further investigations of the impact of ICE on virulence, genome epidemiology, and adaptive genomics of E. anophelis. IMPORTANCE Elizabethkingia anophelis is an opportunistic human pathogen, and the genetic diversity between strains from around the world becomes apparent as more genomes are sequenced. Genome comparison identified three types of putative ICEs in 31 of 36 strains. The diversity of ICEs suggests that they had different origins. One of the ICEs was discovered previously from a large E. anophelis outbreak in Wisconsin in the United States; this ICE has integrated into the mutY gene of the outbreak strain, creating a mutator phenotype. Similar to ICEs found in many bacterial species, ICEs in E. anophelis carry various cargo genes that enable recipients to resist antibiotics and adapt to various ecological niches. The adaptive immune CRISPR-Cas system is present in nine of 36 strains. An ICE-derived spacer was found in the CRISPR locus in a strain that has no ICE, suggesting a past encounter and effective defense against ICE.